2009
DOI: 10.1063/1.3158535
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism induced by Zn vacancy defect and lattice distortion in ZnO

Abstract: Through the full potential linearized augmented plane wave method, we have explored the vacancy defect induced magnetism in wurtize ZnO. It has been found that the Zn vacancy defect brings a spin polarized state in the nearest neighbor oxygen atoms, whereas the oxygen vacancy defect has no influence on the magnetism. However, it is found that the lattice distortion is a crucial factor for the Zn vacancy induced ferromagnetism because the ferromagnetic ground state cannot be achieved if there is no lattice dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…61 The other evidence comes from the recent reports where cation vacancies was suggested to be responsible in establishing the ferromagnetism in wide band gap oxides, 5,31,40,73 Additionally, many recent theoretical calculations suggest that the s electrons contributed by V O cannot establish ferromagnetism. 27,34 These considerations guided us to focus on the role of V Zn in the first-principles calculations which will be detailed in the next section.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…61 The other evidence comes from the recent reports where cation vacancies was suggested to be responsible in establishing the ferromagnetism in wide band gap oxides, 5,31,40,73 Additionally, many recent theoretical calculations suggest that the s electrons contributed by V O cannot establish ferromagnetism. 27,34 These considerations guided us to focus on the role of V Zn in the first-principles calculations which will be detailed in the next section.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…The existance of RFTM in the undoped ZnO stimulated discussion about the role of intrinsic defects in this phenomenon. For the Zn-O system, also known as a pristine oxide, it was shown that defects, such as Zn and O vacancies [16][17][18][19][20][21], Zn interstitials [22], grain boundaries [23] and lattice distortions [24], might contribute to the development of RTFM. If all these defects are indeed responsible for the ferromagnetism in thin films and nanoparticles, they should be thermodynamically stable at least to room temperature, and magnetic exchange interaction between them should be strong enough for the existence of ferromagnetism to be feasible [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the defect species involved in inducing ferromagnetism in one ZnO based DMS system may not be effective in similar others [4,7,20]. The site occupied by the dopant atom [16], its size, electronic configuration and defect decoration [9], lattice strain [21], band gap [5] etc. determines the final and modified band structure of the ZnO host lattice.…”
Section: Introductionmentioning
confidence: 99%